Inversion of Configuration at the Phosphorus Nucleophile in the Diastereoselective and Enantioselective Synthesis of P‐Stereogenic syn‐Phosphiranes from Chiral Epoxides. (23rd March 2018) - Muldoon, Jake A.; Varga, Balázs R.; Deegan, Meaghan M.; Chapp, Timothy W.; Eördögh, Ádám M.; Hughes, Russell P.; Glueck, David S.; Moore, Curtis E.; Rheingold, Arnold L.
Abstract: Nucleophilic substitution results in inversion of configuration at the electrophilic carbon center (SN 2) or racemization (SN 1). The stereochemistry of the nucleophile is rarely considered, but phosphines, which have a high barrier to pyramidal inversion, attack electrophiles with retention of configuration at P. Surprisingly, cyclization of bifunctional secondary phosphine alkyl tosylates proceeded under mild conditions with inversion of configuration at the nucleophile to yield P‐stereogenic syn ‐phosphiranes. DFT studies suggested that the novel stereochemistry results from acid‐promoted tosylate dissociation to yield an intermediate phosphenium‐bridged cation, which undergoes syn ‐selective cyclization.